Design of a spider robot to move motors in an industrial environment - خنيسي, محمد (Latakia University Journal -Engineering Sciences Series, 2025)
This research focuses on the design and development of a spider robot controlled remotely via Bluetooth technology using an Arduino Nano board and SG90 servo motors. The project aims to create a simple educational model that can be utilized to teach students and beginners the fundamentals of programming, electronics, and robotics control. A dedicated mobile application was developed, enabling users to control the robot’s movements effortlessly by sending commands via Bluetooth. The movements include forward, backward, right turn, left turn, and stop. The research adopts a methodology combining engineering design and experimental programming, employing tools such as SolidWorks for the robot’s structural design and Arduino IDE for writing the programming code. The robot was tested in a real educational environment, demonstrating high effectiveness in enhancing students' learning skills. The results also showed the ease of use and cost-effectiveness of the model compared to traditional systems. The study highlights the potential for extending the model to include light industrial applications by integrating advanced sensors to enhance the robot’s performance in various environments. The project offers opportunities for broad applications, including teaching robotics in schools and universities, as well as in industrial settings that require low-cost and easy-to-implement tools. The results present an opportunity to adopt this technology on a wider scale, focusing on improving the programming design and adding intelligent features such as obstacle avoidance and increased operational autonomy for the robot.